Assessment of an evidence-based laryngeal cancer fact sheet: A mixed methods study. (January 2021) - Jabbour, Joe; Shepherd, Heather L; Beddow, Thomas; Sundaresan, Puma; Milross, Chris; Palme, Carsten E; Clark, Jonathan R; Dhillon, Haryana M
To evaluate perceptions of a laryngeal cancer fact sheet amongst people with direct experience of the disease and its treatment. A mixed methods study (questionnaire and interview) evaluating the information resource was conducted across two institutions. In total 20 participants responded to the questionnaire. Overall participants reported the information resource was detailed and understandable. Insufficient information was provided on: impact on family in eight participants (40%); impact on work in six (33%); and, second opinions and long-term side effects in five (25%). The majority (67%) wanted a large amount of information with the preferred source being one-on-one meetings with their doctor. The thematic analysis identified three main themes: preferences for information, self-management; and, information sources. People with direct experience of laryngeal cancer and its treatments reported the information resource was comprehensive and clear. There were some gaps in the information provided, particularly related to survivorship issues.